Review article Psychological aspects of heart failure – beyond depression, anxiety and quality of life - Agnieszka Siennicka; Anna Stromberg; Waldemar Banasiak; Piotr Ponikowski; Ewa Anita Jankowska (Health Psychology Report, 2015)
The progression of heart failure (HF), similarly to other chronic and/or terminal diseases, affects the psychological status of the patients, with consequences for general well-being. The changes in psychological features can be measured and quantified using numerous psychological questionnaires, which do not establish any diagnosis of pathology, although they may be important for the effectiveness of applied treatment of patients with HF. In this paper, we summarize and discuss available evidence on psychological phenomena occurring in the course of HF, such as: ‘Type D’ personality, anxiety, psychological distress, coping strategies, sense of coherence, affectivity, sense of self-efficacy, sense of control and health perception, along with the presentation of available and validated measures of psychological features.